2000
DOI: 10.1152/ajpregu.2000.279.6.r2048
|View full text |Cite
|
Sign up to set email alerts
|

Anticipatory changes in liver metabolism and entrainment of insulin, glucagon, and corticosterone in food-restricted rats

Abstract: Restricted feeding schedules entrain behavioral and physiological circadian rhythms, which depend on a food-entrainable oscillator (FEO). The mechanism of the FEO might depend on digestive and endocrine processes regulating energy balance. The present study characterizes the dynamics of circulating corticosterone, insulin, and glucagon and regulatory parameters of liver metabolism in rats under restricted feeding schedules. With respect to ad libitum controls, food-restricted rats showed 1) an increase in cort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
123
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 118 publications
(136 citation statements)
references
References 29 publications
11
123
1
Order By: Relevance
“…These results are in agreement with previous reports showing that the AAs secondary to RFSs exhibit specific regulatory parameters of liver metabolism (Díaz-Muñoz et al 2000) and support the notion that the physiological state of rats under an RFS is unique and distinct from rats fed freely or fasted for 24 h (Persons et al 1993). Our results confirm previous data on fasting regimens showing that although changes in systemic thyroid status are evident until 48 or 72 h after fasting, liver D1 activity and mRNA content start to decrease within 24 h or less (Reimers et al 1986, O'Mara et al 1993, Kmiec et al 1996.…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…These results are in agreement with previous reports showing that the AAs secondary to RFSs exhibit specific regulatory parameters of liver metabolism (Díaz-Muñoz et al 2000) and support the notion that the physiological state of rats under an RFS is unique and distinct from rats fed freely or fasted for 24 h (Persons et al 1993). Our results confirm previous data on fasting regimens showing that although changes in systemic thyroid status are evident until 48 or 72 h after fasting, liver D1 activity and mRNA content start to decrease within 24 h or less (Reimers et al 1986, O'Mara et al 1993, Kmiec et al 1996.…”
Section: Discussionsupporting
confidence: 94%
“…Moreover, the lack of signal in the long D1 mRNA amplification for all the samples is in agreement with previous work where we demonstrated that the large mRNA form was expressed only in metabolic overdemand situations like chronic hyperthyroidism, lactation or adrenergic stimulation (Aceves & Huidobro 2001), and it suggests that in normal or fasting regimens D1 enzyme is encoded by the short messenger. The low D1 activity measured before food presentation (0800 and 1100 h) was coincident with a significant increase in corticosterone serum levels (Díaz-Muñoz et al 2000), whereas the enhancement in D1 activity after feeding (1400 h) was concurrent with a peak in serum insulin (Díaz-Muñoz et al 2000). These correlations could be part of a possible mechanism to account for the changes in D1 activity in RFS rats, since Davies et al (1996) and Sato et al (1983) reported that hepatic D1 activity is decreased by glucocorticoid administration and stimulated by insulin treatment respectively.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations